Bowel Preparation in Pediatric Colorectal Surgery, Can We Move On? Historical and Literature Review - Kshetra Rinaldhy; Ganesha Wisnu; Ni Made Sarastri Widyani; Ahmad Yani (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Surgical procedure in colorectal cases have a high morbidity rate; in pediatric population, surgical site infection occurs in more than 13% of patients undergoing elective colorectal surgery. Bowel preparation is believed to decrease infection rate by removing feces from colorectal. This procedure has been routinely performed despite the lack of clear evidence and the invasive nature of the procedure. In pediatric population, the evidence is scarce with varying qualities, thus this study aims to evaluate the effect of bowel preparation on pediatric population. Methods: We conducted a comprehensive literature review from PubMed and cross-referencing articles. Six full-text studies presenting bowel preparation in pediatric colorectal surgeries were included in the analysis. Results: Majority of studies we analyzed showed no association between bowel preparation and surgical site infections. They also showed the lack of correlation between the procedure and post-operative complication. Discussion: Bowel preparation was quickly adapted by surgeons due to its theoretical effect, but current evidence showed no clear benefit in doing so. In pediatric cases, the evidence is scarce and variable, and with the risk associated, surgeons should consider carefully before conducting bowel preparation in pediatric patients. Conclusion: Bowel preparation does not significantly decrease post-operative morbidities, such as anastomosis leakage, intrabdominal infection, and surgical wound infection.